2011
DOI: 10.1098/rspb.2010.2673
|View full text |Cite
|
Sign up to set email alerts
|

Parasitoid diversity reduces the variability in pest control services across time on farms

Abstract: Recent declines in biodiversity have increased interest in the link between biodiversity and the provision and sustainability of ecosystem services across space and time. We mapped the complex network of interactions between herbivores and parasitoids to examine the relationship between parasitoid species richness, functional group diversity and the provision of natural pest control services. Quantitative food webs were constructed for 10 organic and 10 conventional farms. Parasitoid species richness varied fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 28 publications
5
45
2
Order By: Relevance
“…Stability of ecosystem functions is thought to increase with species richness due to niche complementarity, facilitation, or sampling effects (Hooper et al, 2005); a positive relationship that has been found for a variety of ecosystem functions including biomass production, crop pollination, and pest control (Garibaldi et al, 2011;Isbell et al, 2009;MacFadyen et al, 2011). Studies linking natural enemy diversity to pest control services have focused on temporal stability, while spatial stability remains largely unexplored although considerable spatial heterogeneity in terms of abundance of natural enemies and their prey have been observed within fields (Holland et al, 2004;Winder et al, 2005;MacFadyen et al, 2011). Because landscape complexity is known to enhance natural enemy diversity and abundance, we expected to find a lower within-field stability (higher variability) in pest control in simple compared with more complex landscapes.…”
Section: Discussionmentioning
confidence: 99%
“…Stability of ecosystem functions is thought to increase with species richness due to niche complementarity, facilitation, or sampling effects (Hooper et al, 2005); a positive relationship that has been found for a variety of ecosystem functions including biomass production, crop pollination, and pest control (Garibaldi et al, 2011;Isbell et al, 2009;MacFadyen et al, 2011). Studies linking natural enemy diversity to pest control services have focused on temporal stability, while spatial stability remains largely unexplored although considerable spatial heterogeneity in terms of abundance of natural enemies and their prey have been observed within fields (Holland et al, 2004;Winder et al, 2005;MacFadyen et al, 2011). Because landscape complexity is known to enhance natural enemy diversity and abundance, we expected to find a lower within-field stability (higher variability) in pest control in simple compared with more complex landscapes.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of predator or parasitoid species richness on prey attack rates and stability have been tested previously (e.g., Cardinale et al 2003, Ives et al 2005, Snyder et al 2006, Tylianakis et al 2006, Macfadyen et al 2011, and we were interested here in whether trophic complementarity and redundancy provide more information than does simple, and more easily measured, species richness. Therefore, we also incorporated, in all the models, host species richness, parasitoid species richness, and the weighted number of different interactions (quantitative connectance; Bersier et al 2002) as covariates, so that we could test for effects of interaction structure on parasitism rates after accounting for the effects of the number of species in webs and the number of links between species.…”
Section: Analysesmentioning
confidence: 99%
“…; Macfadyen et al . ; Brittain, Kremen & Klein ). This is true for the stability of pollination services; if complementary pollinator functional groups visit different plant species, or the same plant species at different times, this can enhance the overall visitation and pollination of plant communities (Hoehn et al .…”
Section: Introductionmentioning
confidence: 99%